г.

  1. A) , .
  2. IV. г .
  3. ij г . ij г .
  4. .
  5. ̳ , .
  6. ̳ , .
  7. .

32) z = f (x; y) (0; y0), ֳ .

- z = f (x; y) (0; y0),

- z = f (x) (0; y0).

33) f (x) . X0 f (x) ֳ . : - , .

34) u = f (x), v = g (x) x0, , , ( g (x) 0) x0, :

u, v, u + v, uv, u / v, x0, :

, , d (u + v) du + dv. ij, d (u + v) = (u + du) + (v + dv) - (u + v) = du + dv. . :

35)1)( ) y = f (x) x0 ֳ . , :

2)

. y = f (x) x0, x0

, - - , .

.

36)ij 0 ֳ , .

df (0) = F '(0) ?; ? = d ; df (0) = F '(0) D

37) . 36 +



ղ |

ֳ :

˲Ҳ | ֲ | Ͳ ֲ | | , , ز | ˲Ҳ | Ͳ ֲ | Ͳ , | ֲ | |

© um.co.ua -